Collybiopsis bambusicola sp. nov. in Yunnan Province, Southwestern China - Zhang, Qiu-Yue; Zhou, Meng; Shi, Feng-Ming; Si, Jing; Li, Hai-Jiao (Phytotaxa, 2023)
Collybiopsis bambusicola sp. nov. is described and illustrated from Yunnan Province, Southwestern China, based on morphology and molecular phylogenetic analyses. It is characterized by its minute, cream to cinnamon basidiomata, short, eccentric stipe, forked lamellae, nearly poroid hymenophore which are radially arranged from the base of the stipe, 2–spored basidia, oblong ellipsoid basidiospores (6–8.3 × 3–4.3 μm), and gregarious on dead bamboo. In ITS + nLSU based phylogeny, the new species formed a distinct lineage nested within Collybiopsis ramealis complex clade.